Predictors Of Consumers’ Choice Of Buying Outlets In Imo And Abia States, Nigeria - Onyeagwara, Chukwuemeka A.; Agu, Godswill A.; Aja, Ebeke Egele (Archives of Business Research, 2019)
This study examines the predictors of consumer choice of buying outlet using shoppers in Imo and Abia States. The predictors were modeled as outlet attributes, demographic attribute and product attribute. A sample size of 272 was used for the study while questionnaire served as the data collection instrument. Stated hypotheses were tested with multiple regression analysis in SPSS version 20. Findings revealed that the three predictors (product, outlet and demographic attributes) are significant predictors of choice of buying outlets by consumers. Further analysis however showed that parking space and price which are variables under outlet and product attributes respectively are not significant predictors of choice of shopping outlet. The study recommended among others that shop owners and managers should monitor closely the variables disclosed as significant predictors while striving to adopt the conceptual model of predictors presented in this work.